Early seed development requires the A-type ATP-binding cassette protein ABCA10. Issue 1 (15th February 2022) - Shin, Seungjun; Chairattanawat, Chayanee; Yamaoka, Yasuyo; Yang, Qianying; Lee, Youngsook; Hwang, Jae-Ung
Abstract: A-type ATP-binding cassette (ABCA) proteins transport lipids and lipid-based molecules in humans, and their malfunction is associated with various inherited diseases. Although plant genomes encode many ABCA transporters, their molecular and physiological functions remain largely unknown. Seeds are rapidly developing organs that rely on the biosynthesis and transport of large quantities of lipids to generate new membranes and storage lipids. In this study, we characterized the Arabidopsis ( Arabidopsis thaliana ) ABCA10 transporter, which is selectively expressed in female gametophytes and early developing seeds. By 3 d after flowering (DAF), seeds from the abca10 loss-of-function mutant exhibited a smaller chalazal endosperm than those of the wild-type. By 4 DAF, their endosperm nuclei occupied a smaller area than those of the wild-type. The endosperm nuclei of the mutants also failed to distribute evenly inside the seed coat and stayed aggregated instead, possibly due to inadequate expansion of abca10 endosperm. This endosperm defect might have retarded abca10 embryo development. At 7 DAF, a substantial portion of abca10 embryos remained at the globular or earlier developmental stages, whereas wild-type embryos were at the torpedo or later stages. ABCA10 is likely involved in lipid metabolism, as ABCA10 overexpression induced the overaccumulation of triacylglycerol but did not change the carbohydrate or protein contents in seeds. In agreement, ABCA10 localized to the endoplasmic reticulum (ER), the major site of lipid biosynthesis. Our results reveal that ABCA10 plays an essential role in early seed development, possibly by transporting substrates for lipid metabolism to the ER. Abstract : Mutation in an A-type ABC transporter gene causes defects in endosperm development in young growing seeds, and its overexpression increases seed lipid content.